EFEITOS DA ARBORIZAÇÃO URBANA VIÁRIA SOBRE O CONFORTO TÉRMICO – Estudo de caso em Pará de Minas – Minas Gerais - Alba Valéria Sandi Mascarello (2017)
The sudden growth of populations and the built environment in cities has imposed severe transformations in urban environments. This accelerated pace does not allow nature to recover properly, which compromises water resources, minerals and plants, with direct consequences on the life of living beings in general and of man in particular. Such fact compromised urban planning in terms of land use, making cities more arid and hot, a fact aggravated by lenient legislation on urban afforestation. In this research, the study of urban afforestation in general and of the road afforestation, in particular, aims to evaluate the possibility of improving thermal comfort in urban environments through the preservation / implantation / maintenance of urban vegetation, especially arboreal vegetation. The methodological procedures used from data collection in four areas of the city of Pará de Minas are measured in the field in areas of presence and absence of arboreal vegetation, microclimatic variables - temperature, humidity and direction and air velocity in addition to incident radiation found through Radiasol ® software; description of the arboreal species present in the study areas - Oiti (Licania tomentosa) and Sibipiruna (Caesalpinia peltophoroides), as well as their current conditions; indicators for assessing the efficiency of arboreal vegetation in thermal comfort by means of indexes such as Arboreal Shading Index (ISA), Leaf Area Index (IAF), hemispheric photos and flat photos, shadow simulation projected by afforestation in the urban environment - Sketchup images ® and PET Index (Physiological Equivalent Temperature) considering the extinction of radiation from the tree canopy. The results show the effective contribution of urban afforestation to the decrease of temperature and improvement of comfort conditions in urban environments, especially during the hottest times of the day. The two species analyzed, Oiti (Licania tomentosa) and Sibipiruna (Caesalpinia peltophoroides) showed significant reduction of temperatures in their respective areas of activity, both indicating the thermal perception considered 'comfortable' by the PET index, while at the same time, the thermal perception was of 'very hot', highlighting the significant differences with great contrasts in the presented temperature values. The results show that the trees offer a great potential of regulation of the microclimate in their surroundings and it is concluded that there is a need for the preservation, implantation and correct maintenance of the urban tree-planting in the cities, as a measure of obtaining the thermal comfort and mitigation of the climate adverse conditions. It was also noticed, during this research, the fundamental importance of good planning in terms of urban afforestation and updating of existing legislation on this topic.